Online based Business Partnership Consumer Protection - Widaningsih, W (Universitas Muhammadiyah Surakarta, 2024)
The internet has brought the world economy into a new chapter that is more popularly known as the digital economy. Its progress has a positive impact in facilitating product marketing so that it can save costs and time. In business, there is a partnership between business actors and e-commerce. The type of research is normative legal research. Using a legislative approach and a case approach. Collecting legal materials by recording and documenting primary legal materials, namely laws and regulations, secondary legal materials such as books, articles. Using a deductive method, namely from general to specific. The descriptive method is by describing or explaining problems, providing reviews, views, and solutions to the problems being studied, which are then drawn to a conclusion. The conclusion is that online-based businesses today and especially in the jurisdiction of Indonesia have grown rapidly. Indonesia already has a legal basis, namely Law Number 8 of 1999 concerning Consumer Protection in addition to the existence of other laws and regulations that regulate the same thing. Consumers in terms of their business partnerships must be given various special protections which are very vulnerable to various possibilities that will harm the consumers themselves from business actors who do not have good intentions in carrying out online-based business partnerships. If there are problems between consumers and business actors in carrying out partnerships, they can use the UUPK facility which is a guideline for consumers, especially to fight for their rights to protect their interests.